The carrying : poems - Limón, Ada (Milkweed Editions, 2018)
"Vulnerable, tender, acute, these are serious poems, brave poems, exploring with honesty the ambiguous moment between the rapture of youth and the grace of acceptance. A daughter tends to aging parents. A woman struggles with infertility--"What if, instead of carrying / a child, I am supposed to carry grief?"--And a body seized by pain and vertigo as well as ecstasy. A nation convulses: "Every song of this country / has an unsung third stanza, something brutal." And still Limón shows us, as ever, the persistence of hunger, love, and joy, the dizzying fullness of our too-short lives. "Fine then, / I'll take it," she writes. "I'll take it all." In Bright Dead Things, Limón showed us a heart "giant with power, heavy with blood"--"the huge beating genius machine / that thinks, no, it knows, / it's going to come in first." In her follow-up collection, that heart is on full display--even as The Carrying continues further and deeper into the bloodstream, following the hard-won truth of what it means to live in an imperfect world."--Publisher's website.